The Influence of Work Experience and Organizational Culture on Employee Performance - Badrianto, Yuan; Suwandi, Suwandi; Astuti, Dwi (Lentera Ilmu Nusantara, 2024)
This study aims to analyze the influence of work experience and organizational culture on employee performance in manufacturing companies in the Bekasi area. In an era of increasingly fierce global competition, an in-depth understanding of the factors that affect employee performance is crucial to the success of an organization. Using a quantitative approach, this study involved 54 respondents from various manufacturing companies in Bekasi. Data was collected through a questionnaire with a Likert scale of 1-5 and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS. The results of the study show that both work experience and organizational culture have a positive and significant influence on employee performance. Organizational culture contributes more than work experience to the variation in employee performance. These findings highlight the importance of a comprehensive HR development strategy, including improving employee experience and strengthening organizational culture. This research contributes to the development of HR and organizational management theory, as well as provides practical implications for manufacturing companies in improving the performance of their employees. Research limitations and suggestions for further studies are also discussed.